Biochemical composition and mapping of definitive protein ions of a somatic extract from Trichinella spiralis - G. V. Konovalova; S. V. Aleshin (Российский паразитологический журнал, 2025)
The purpose of the research is to study the biochemical composition and mapping of the main protein peaks of the total somatic extract from Trichinella spiralis larvae isolated from the muscle tissue of infected rats and mice.Materials and methods. The experiments were conducted on mature outbred rats and mice (males). To obtain the somatic extract, the animals were infected with T. spiralis larvae intragastrically at a rate of 10 larvae per 1 g of body weight. The extract was prepared from Trichinella sp. larvae isolated from the carcasses of the infected rats and mice. A study was conducted of the biochemical composition of the protein extract of T. spiralis isolated from the muscle tissue of infected rats; 25 parameters were determined. In a comparative aspect, the mapping was completed for definitive protein ions in total somatic Trichinella sp. extracts obtained from two types of laboratory animals, rats, and mice using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS).Results and discussion. Total and direct bilirubin, urea, creatinine, total protein, globulin, glucose, triglycerides and electrolytes were found in the total somatic extract of T. spiralis; the activity of a number of enzymes (AST, ALT, alkaline phosphatase and gamma glutamine transferase) was also detected. All detected metabolites were at a lower level (or absent) versus the reference values of the healthy rats’ blood except for higher creatinine in the Trichinella sp. extract. The results of mapping definitive protein ions in two somatic extract samples obtained from larvae isolated from muscle tissue of the infected rats and mice indicate high similarity to conclude that the proteins of these extracts are structurally close.